In Vivo Tomographic Imaging of Deep-Seated Cancer Using Fluorescence Lifetime Contrast - Rice, William L.; Shcherbakova, Daria M.; Verkhusha, Vladislav V.; Kumar, Anand T.N. (Cancer research (Chicago, Ill.), 2015)
Preclinical cancer research would benefit from noninvasive imaging methods that allow tracking and visualization of early-stage metastasis in vivo. Although fluorescent proteins revolutionized intravital microscopy, two major challenges that still remain are tissue autofluorescence and hemoglobin absorption, which act to limit intravital optical techniques to large or subcutaneous tumors. Here, we use time-domain (TD) technology for the effective separation of tissue autofluorescence from extrinsic fluorophores, based on their distinct fluorescence lifetimes. In addition, we use cancer cells labeled with near infrared fluorescent proteins (iRFP) to allow deep-tissue imaging. Our results demonstrate that TD imaging allows the detection of metastasis in deep-seated organs of living mice with a more than 20-fold increase in sensitivity compared with conventional continuous wave techniques. Furthermore, the distinct fluorescence lifetimes of iRFPs enable lifetime multiplexing of three different tumors, each expressing unique iRFP labels in the same animal. Fluorescence tomographic reconstructions reveal three-dimensional distributions of iRFP720-expressing cancer cells in lungs and brain of live mice, allowing ready longitudinal monitoring of cancer cell fate with greater sensitivity than otherwise currently possible. Cancer Res; 75(7); 1236–43. ©2015 AACR.